2014
DOI: 10.11118/actaun201058020045
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the co-application of Promalin® at different bud phenological stages and notching at different distances on lateral branching of three sweet cherry cultivars (Prunus Avium L.) in central Chile

Abstract: BENNEWITZ, E., FREDES, C., GUTIERREZ, L., LOŠÁK, T.: Eff ect of the co-application of Promalin® at different bud phenological stages and notching at diff erent distances on lateral branching of three sweet cherry cultivars (Prunus Avium L.) in central Chile. Acta univ. agric. et silvic. Mendel. Brun., 2010, LVIII, No. 2, pp. 45-50

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Veinbrants and Miller (1981) also reported that the application of Promalin increased the number of shoots from 4 to 11. Bennewitz et al (2010) found that in treated Lapins trees, the total number of lateral shoots (in most cases) significantly increased, while in Stella trees, the total feather length and the total number of lateral shoots were not affected by Promalin treatments. Jacyna et al (1989) suggested that Promalin increased both shoot and spur numbers in sweet cherries.…”
Section: Resultsmentioning
confidence: 84%
“…Veinbrants and Miller (1981) also reported that the application of Promalin increased the number of shoots from 4 to 11. Bennewitz et al (2010) found that in treated Lapins trees, the total number of lateral shoots (in most cases) significantly increased, while in Stella trees, the total feather length and the total number of lateral shoots were not affected by Promalin treatments. Jacyna et al (1989) suggested that Promalin increased both shoot and spur numbers in sweet cherries.…”
Section: Resultsmentioning
confidence: 84%
“…Summer notching did not increase branching. Greene and Autio (1994), Elfving and Visser (2007), Atay and Koyuncu (2013), andvon Bennewitz et al (2014) reported increased branching when late winter notching was used. The higher shoot numbers recorded in combined treatments with summer notching were a reaction to the preceding application of pinching or phytohormones.…”
Section: Discussionmentioning
confidence: 95%
“…Leaf pinching is a mechanical method that removes (by pinching out) some of the youngest leave blades while the growing tip (meristem) stays intact (Neri et al 2004). Another mechanical method that occasionally can be used for prolepsis induction is the notching of one-year-old whips at the end of winter (Greene, Autio 1994;Elfving, Visser 2007;von Bennewitz et al 2014). This technique is nevertheless labour-demanding, extends the growing period in the nursery by one year, and may increase susceptibility to disease infections such as bacterial canker (Pseudomonas syringae) in some climates.…”
Section: Leaf Pinching and Phytohormones -Two Important Components For The Branching Induction On Sweet Cherrymentioning
confidence: 99%
“…The branching potential increases when the cuttings are processed with growth regulators whose active substances are 1.8% GA4+7+1.8% 6-BA, GA4 or GA4+7 (Bennewitz 2010, Peșteanu & Bostan 2018, Toprak et al 2018 in the ratio of one part of product and 8-10 parts of paint per latex base (Long et al 2014, Long et al 2020, Peșteanu 2021.…”
Section: Introductionmentioning
confidence: 99%